Transmisi dan Faktor Risiko Infeksi Helicobacter pylori pada Gastritis: Literature Review: Transmisi dan Faktor Risiko Infeksi Helicobacter pylori pada Gastritis: Literature Review - Dharmesti, Rizky Aleyda; Utama, Winda Trijayanthi; Wijaya, Sofyan Musyabiq; Sukohar, Asep (Medula, 2025)
Gastritis a common health issue with high prevalence both globally and nationally. Acute gastritis often associated with lifestyle factors and stress, while chronic gastritis is primarly caused by infection of Helicobacter pylori. This review aims to provide a detail understanding of Helicobacter pylori transmission and risk factor for its infection. This review is a narrative literature review that comparing multiple studies about the topic. Literature was gathered from various database and analyzed to find relevant findings. Result of this study indicate that Helicobacter pylori transmission occurs trough multiple routes such as fecal-oral and oral-oral. Hygiene status and sociodemographic conditions are the most significant risk factor that influence this infection. Chronic gastritis a prevalent condition often caused by Helicobacter pylori infection. Risk factors for this infection include low socioeconomic status, poor hygiene, inadequate sanitation, and exposure to contaminated environments. H. pylori bacteria can persist for extended periods in specific environments, such as water, food, and dairy products, but struggle to survive in acidic conditions, such as found in yogurt. The prevalence of infection notably higher among children living in areas with poor sanitation and unhygienic food practices. Prevention strategies involve enhancing hygiene standards, improving sanitation, ensuring access to clean water, and promoting health education to minimize the risk of transmission. Early treatment is crucial to restore the gastric mucosa's health and prevent further damage.